Feasibility Study of Uniform Residual Stress Measurement Using the Hole-Drilling Method and Digital Image Correlation - Halabuk, Dávid; Vajdák, Michal; Návrat, Tomáš (My University, 2025)
Background The hole-drilling method, widely used to evaluate near-surface residual stresses, typically relies on strain gauge rosettes to measure surface deformations resulting from stress relaxation. However, this approach has several limitations, including a small number of discrete measurement points, the need for careful surface preparation, and sensitivity to misalignment between the rosette and the drilled hole. Objective To address these issues, the use of Digital Image Correlation (DIC), a full-field optical measurement technique, was investigated as a replacement for the strain gauge rosette within the hole-drilling method. Methods DIC was employed to measure strain and displacement fields around drilled holes in steel specimens subjected to various load levels, aiming to identify the minimum stress that could be accurately resolved. Several adjustments were made to both the hardware configuration and data processing procedures within the DIC setup to improve the accuracy of measured deformation. Results Accurate stress evaluation was achieved even at low stress levels, on the order of a few MPa, despite the relatively small strain magnitudes compared to the noise level. Conclusions The results obtained demonstrate that integrating DIC with the hole-drilling method offers a promising and effective alternative to traditional strain gauge-based residual stress measurement.

Background The hole-drilling method, widely used to evaluate near-surface residual stresses, typically relies on strain gauge rosettes to measure surface deformations resulting from stress relaxation. However, this approach has several limitations, including a small number of discrete measurement points, the need for careful surface preparation, and sensitivity to misalignment between the rosette and the drilled hole. Objective To address these issues, the use of Digital Image Correlation (DIC), a full-field optical measurement technique, was investigated as a replacement for the strain gauge rosette within the hole-drilling method. Methods DIC was employed to measure strain and displacement fields around drilled holes in steel specimens subjected to various load levels, aiming to identify the minimum stress that could be accurately resolved. Several adjustments were made to both the hardware configuration and data processing procedures within the DIC setup to improve the accuracy of measured deformation. Results Accurate stress evaluation was achieved even at low stress levels, on the order of a few MPa, despite the relatively small strain magnitudes compared to the noise level. Conclusions The results obtained demonstrate that integrating DIC with the hole-drilling method offers a promising and effective alternative to traditional strain gauge-based residual stress measurement.
Feasibility Study of Uniform Residual Stress Measurement Using the Hole-Drilling Method and Digital Image Correlation
Keywords: Hole-drilling method; Residual stress; Digital image correlation; Full-field measurement; Hole-drilling method; Residual stress; Digital image correlation; Full-field measurement